Persepsi Audiens terhadap Konten Kesehatan dan Kecantikan di Tiktok: Tinjauan Literatur Perspektif Teori Persepsi Bernard Berelson - Nabila Indah Rahmawati; Putu Riana Artyanti Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of social media has shifted the way society receives and processes information, including in the fields of health and beauty. TikTok, with its engaging and interactive short video format, has become an important platform for users to search for, share, and evaluate such information. However, audiences' perceptions of this content can vary depending on how they observe, pay attention to, and interpret the information presented. This article reviews the scientific literature discussing audience perception of health and beauty content on TikTok, based on Bernard Berelson's perception theory, which includes the components of sensation, attention, and interpretation. The literature review method examines relevant national and international publications to identify factors that influence perception and their implications on trust, aesthetic standards, and audience behavior. The findings indicate that source credibility, content presentation quality, and the platform's algorithm characteristics are the main determinants of how audiences form their perceptions of the content. In addition, other factors such as content relevance to personal preferences, audience interaction with content creators, and the influence of user communities also affect how this information is processed and accepted. The implications of these findings highlight the importance of transparency and responsibility in creating and distributing health and beauty content on social media to ensure that audiences receive accurate and accountable information.